Performance Analysis of an Off-Grid System in The Gambia: A Case Study of a 120 kWp Solar Installation at Nyamanarri Village - (:unkn) unknown (My University, 2025)
Aims: Despite recent improvements, providing universal access to electricity is still a significant problem in many sub-Saharan African nations, especially in rural areas. Due to this difficulty, solar photovoltaic (PV) mini-grid systems have become a viable off-grid electrification option. Their actual effectiveness and dependability in practical applications, however, are not well understood. This study investigates the dependability and performance of a 120 kWp off-grid photovoltaic mini-grid system erected in a remote village in The Gambia using real-time monitored data and IEC's evaluation standard. Place of Study: A 120 kWp off-grid PV mini-grid was built in Nyamanarri (130 20’ 03” North and 130 52’ 08” West) in the Upper River Region of The Gambia. Methodology: The study was based on data on energy production as a function of energy generation and consumption from 1st April 2022 to 31st March 2023. Analysis was carried out using R software to obtain some results. Results: The results revealed that the mini-grid generated 449.98 kWh of electricity per day, which was 570.02 kWh fewer than the predicted 1020 kWh per day (62.54% less). The load, on the other hand, received 87.3% of the average daily electrical generation. The differences can be explained by system losses of 14.48 kWh/kWp/month and average PV capture losses of 62.87 kWh/kWp/month. The findings of the performance evaluation showed that the mini-grid system is not doing well; the average on-site module efficiency (ηpc), performance ratio (PR), capacity factor (CF), and overall system efficiency (ηsys) were 12.4 %, 56.37 %, 13.644 % and 19.53 %, respectively. The daily PV energy output was found to be insufficient to fulfill the daily demand. Consequently, the load shedding is 12 hours every day, from 13:00 to 15:00 and again 18:00 to 19:00 and again from 1:00 to 10:00. Conclusion: To ensure high performance and reliability of off-grid PV mini-grid systems, the study showed th
Keywords: African Research